Agricultural Cooperatives from Uzbekistan and Their Activities (1917-1929 Years) (Eurasian Scientific Herald, 2022)
This article describes the new economic policy imposed by the Bolsheviks in Uzbekistan in 1917-1929 after the Great October Socialist Revolution in Russia in 1917, its role and consequences in the social, economic, political, and cultural spheres of our country